2020
DOI: 10.3390/diagnostics10100759
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Analysis of Resistant Helicobacter pylori Strains Isolated from Children with Gastrointestinal Diseases

Abstract: Antibiotic resistance of Helicobacter pylori is currently a global issue. The aim of this study was to analyze actual antibiotic resistance rates of H. pylori strains isolated from children with primary infections and to compare the incidence of mutations that determine resistance to clarithromycin (CH) and metronidazole (MET) in children with different clinical diagnoses. A total of 91 H. pylori strains were isolated from 108 children with primary infections. Drug susceptibility testing of the strains was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…In agreement to our findings, the CLR-R rate in H. pylori resistant strains isolated from children in China was 36.7% (29/79) with A2143G mutation being the most common 82.8% (24/29) [32]. Moreover, in another recent study carried out on children in Wroclaw Medical University found that CLR-R was 68% and A2143G was the most frequently detected mutation 61% (38/62) [33].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement to our findings, the CLR-R rate in H. pylori resistant strains isolated from children in China was 36.7% (29/79) with A2143G mutation being the most common 82.8% (24/29) [32]. Moreover, in another recent study carried out on children in Wroclaw Medical University found that CLR-R was 68% and A2143G was the most frequently detected mutation 61% (38/62) [33].…”
Section: Discussionsupporting
confidence: 91%